New host records and descriptions of five new species of Myrsidea Waterston, 1915 (Phthiraptera: Menoponidae) from passerine birds (Aves: Passeriformes) - Valim, Michel P.; Price, Roger D.; Johnson, Kevin P. (Zootaxa, 2011)
Three species of previously described Myrsidea from the birds Lochmias nematura obscurata Cabanis, Automolus ochrolaemus (Tschudi, 1844) (both Furnariidae) and Pachyramphus cinnamomeus Lawrence, 1861 (Cotingidae) are redescribed, including new host and geographical records. Five new species of Myrsidea from the Neotropics are described and illustrated. These species and their type hosts are: M. waterstoni n. sp. from Anabacerthia variegaticeps (Sclater), M. meyi n. sp. from Syndactyla subalaris (Sclater) (Furnariidae), M. dalgleishi n. sp. from Glyphorynchus spirurus (Vieillot) (Dendrocolaptidae), M. cicchinoi n. sp. from Rhynchocyclus olivaceus (Temminck) (Tyrannidae), and M. castroae n. sp. from Atlapetes albinucha gutturalis (Lafresnaye) (Emberizidae). Sequences of a portion of the mitochondrial cytochrome oxidase I (COI) gene for four of these new species were highly divergent from those of other species of Myrsidea.